Correlation of Exclusive Breastfeeding and Complementary Feeding History with Stunting in Children 24-47 Months - Ana Hairunnisak; Siti Rahayu Nadhiroh (Humanistic Network for Science and Technology (HNST), 2021)
Stunting is a kind of condition where toddlers have less length or height than their age. The percentage of stunting in Indonesia is still high and becomes a health problem. Stunting occurs due to several factors. One of which is lack of nutritional intake for infants. The purpose of this study was to analyze the correlation between a history of exclusive breastfeeding and complementary feeding with stunting in children aged 24-47 months. The type of this research was observational analytic with cross-sectional design. Data were collected by filling out a questionnaire by the respondents and analyzed using the chi-square test. The results of this study showed that there was no correlation between the history of exclusive breastfeeding and complementary feeding with stunting. However, there are other factors that influence the occurrence of stunting, consisting of expenditure on food consumption (p=0.007), birth weight (p=0.035), and birth length (p=0.004).Keywords: exclusive breastfeeding; complementary feeding; stunting; toddler